Surface photochemistry: Photodegradation study of pyrene adsorbed onto microcrystalline cellulose and silica - A. S. Oliveira; L. F. Vieira Ferreira; J. P. Da Silva; J. C. Moreira (International Journal of Photoenergy)
Ground-state diffuse reflectance, time resolved laser-induced luminescence, diffuse reflectance laser flash-photolysis transient absorption and chromatographic techniques were used to elucidate the photodegradation processes of pyrene adsorbed onto microcrystalline cellulose and silica. Ground-state diffuse reflectance showed that on both substrates low concentrations display absorption of pyrene monomers. At high concentrations spectral changes attributed to aggregate formation were observed. Laser induced fluorescence showed that pyrene onto microcrystalline cellulose mainly presents fluorescence from monomers, while for silica, excimer-like emission was observed from low surface loadings (≥0.5 μmol g−1). Transient absorption and photodegradation studies were performed at concentrations where mainly monomers exist. On silica, pyrene presents transient absorption from its radical cation. On microcrystalline cellulose both radical cation, radical anion and pyrene triplet-triplet absorption were detected. Irradiation followed by chromatographic analysis showed that pyrene decomposes on both substrates. For pyrene on microcrystalline cellulose 1-hydroxypyrene was the main identified photoproduct since in the absence of oxygen further oxidation of 1-hydroxypyrene was very slow. For pyrene on silica photodegradation was very efficient. Almost no 1-hydroxypyrene was detected since in the presence of oxygen it is quickly oxidized to other photooxidation products. On both substrates, pyrene radical cation is the intermediate leading to photoproducts and oxygen it is not involved in its formation.